Author Correction: Gα13 negatively controls osteoclastogenesis through inhibition of the Akt-GSK3β-NFATc1 signalling pathway - Mengrui Wu (Nature Portfolio, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.